Nine year of Mass Transport Data in the Eastern Boundary of the North Atlantic Subtropical Gyre - Fraile-Nuez, Eugenio; Machín, F.; Vélez-Belchí, Pedro; López-Laatzen, Federico; Borges, R.; Hernández-Guerra, Alonso; Benítez-Barrios, Verónica María (Journal of Geophysical Research, 2010)
[1] One of the longest current meter time series in the Lanzarote Passage in the eastern boundary of the North Atlantic Subtropical Gyre has been used to determine and quantify the 9-year mean transport, the inter-annual and seasonal mass transport variability for the three water masses present in the area. Results show North Atlantic Central Water (NACW) flowing southward in the upper levels with a mean mass transport of −0.81 ± 1.48 Sv, Antarctic Intermediate Water (AAIW) flowing northward at intermediate levels with a mean transport of +0.09 ± 0.57 Sv and Mediterranean Water (MW) flowing southward in the deep part of the passage with a mean transport of −0.05 ± 0.17 Sv. Harmonic and wavelet analysis show the presence of a seasonal pattern in the passage for the three water masses. A maximum southward transport in winter and spring has been observed for the NACW followed by a minimum in summer and fall. Near zero values during winter and spring are found for AAIW, with a maximum northward value in summer and a negative value in fall, when this water mass reverses its flow. MW has a similar seasonal pattern to NACW. The vertical structure in the Lanzarote Passage can be approximated by four significant oscillatory modes which cumulatively explain 86.4% of the variance. The strong transport fluctuation found at the seasonal and inter-annual timescales demonstrates that the Eastern Boundary Current transport has a strong impact on meridional overturning estimates, thus indicating that to understand Meridional Overturning Circulation variability, these transport estimates at the eastern Atlantic margin are necessary.